Sudden Deaths in Mthatha Area of South Africa - Bl Meel (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: A sudden unexpected death in South Africa is considered an unnatural death, and requiresan autopsy to determine the cause of death. These deaths were classified under a vague term, collapse, byinvestigating officers and relatives of the deceased.Objectives: To assess the incidence of sudden deaths in Mthatha.Method: This is a record review from 1993 to 2004 of the medico legal autopsies in Umtata GeneralHospital (UGH). All cases of unnatural deaths are brought by police to UGH mortuary.Results: Four hundred and thirteen cases of sudden deaths were recorded over a period of 12 years (1993-2004) with an average of 11 deaths/100 000 population. The highest (22.7/100 000) was recorded in 1997,and the lowest (4.5/100 000) in 1996. Males outnumbered females 3.2:1. The commonest age group involvedis between 31 and 40 years. The commonest underlying cause of death is pneumonia.Conclusion: There is an increasing trend of sudden deaths in the population in Mthatha and it is mostprevalent among males between 31 and 40 years.